Analysis of Large Graphs - Erciyes, K (Guide to Graph Algorithms, 2018)
Analysis of these graphs requires introduction of new parameters and methods conceptually different than the ones used for relatively smaller graphs. We describe new parameters and methods for the analysis of these graphs and also describe various models to represent them in this chapter. Two widely used models for the large graphs representing real networks are small-world and scale-free models. The former means the average distance between any two nodes in large graphs is small and only few nodes with high degrees exist with majority of the nodes having low degrees in the latter.